EFFECTS OF CHITOSAN NANOPARTICLES AND MS MEDIUM ON POTATO (Solanum tuberosum) SYNTHETIC SEED REGENERATION - Tazkia Khansa Mahira; Susiyanti; Sulastri Isminingsih; Zahratul Millah (UIN Sunan Gunung Djati Bandung, 2026)
This study was conducted to determine the in vitro regeneration response of synthetic potato (Solanum tuberosum L.) plantlet seeds to different concentrations of chitosan nanoparticles and MS medium. The study was conducted at the Plant Physiology and Biotechnology Laboratory of Sultan Ageng Tirtayasa University from December 2025 to April 2026. This study used a factorial randomized block design (RAK) consisting of two factors. The first factor was chitosan nanoparticle (C) with levels of concentration were 0 ppm, 50 ppm, 100 ppm, 150 ppm. The second factor was MS medium (T) with levels of ½ MS, ¼ MS, 0 MS. The results showed that the number of germinated seeds in the 50 ppm + ½ MS medium treatment combination yielded a higher average value of 0.6 seeds. Plant height showed that the 150 ppm + ½ MS medium treatment had the best effect, at 1.05 cm. The success rate of synthetic seed regeneration reached 26.7% in the 50 ppm + ½ MS medium treatments. The study showed that neither treatment had a significant effect on any of the observed parameters.